Inspección visual de la vía que conduce del municipio de la palma cundinamarca a la vereda murca entre el km 3 y 4 (2022)
Today the road that connects the municipality of La Palma Cundinamarca with the village of Murca is in deterioration, which makes it difficult for the socioeconomic activity of the population to improve, Due to this, a visual inspection of the damages that affect both lanes arranged for vehicular traffic between kilometer 3 and 4, which is one of the most deteriorated, is carried out in order to share all the data collected and its analysis with the municipal mayor's office so that they can have a reference monograph, which will allow them to start the proper maintenance of the road and achieve a balance in the socioeconomic part of the population of both La Palma Cundinamarca and the Murca village.